Religious expression in the workplace and the contested role of law - Hambler, Andrew (Milton Park, Abingdon, Oxon : Routledge, 2015)
'The role of religion in various domains of the public sphere provokes much debate. One of the key areas where this debate is unfolding is in the secular workplace, where some employees strongly desire to express their religious beliefs in ways which may bring them into conflict with their employers. For example, a Sikh woman may wish to wear a kara bracelet contrary to an employers uniform policy; or a Muslim may wish to take time out of required working hours for Friday prayers. Equally, some employees may feel compelled to object to particular aspects of their job role from which a crisis of conscience arises. For instance, a Christian registrar might object to registering a same-sex marriage or civil partnership; or a Muslim retail worker might object to handling alcohol.This addresses these conflicts and the role of law in resolving them. It considers what is meant by religious expression by individual employees, and the motives underlying it, and sets out the different ways it might have an impact on the workplace, in both uncontroversial and potentially controversial ways. The book identifies different principled responses to workplace religious expression within a liberal state. It then goes on to analyse to what extent the law in England and Wales reflects these differing responses, both at a legislative and policy level, and at a court and tribunal level. The book determines the extent to which freedom of religious expression for the individual enjoys legal protection in the workplace in England and Wales, and whether or not there is a case for changing the law to strengthen that protection'--
'The workplace is a key area where the issue of religion and its position in the public sphere is under debate. Desires to observe and express religious beliefs in the workplace can introduce conflict between employees and employers. This book addresses the role the law plays in the resolution of these potential conflicts. The book considers the definition and underlying motives of religious expression, and explores the different ways it may impact the workplace. Andrew Hambler identifies principled responses to workplace religious expression with a liberal state and compares this to the state of the law in England and Wales at a court and tribunal level. The book determines the extent to which freedom of religious expression for the individual enjoys legal protection in the workplace in England and Wales, and asks whether there is a case for changing the law to strengthen that protection. The book will be of great use and interest to scholars and students of religion and the law, employment law, and religion and human rights'--
Introduction -- Conceptualishing'religious expression' in the workplace -- Restricting or guaranteeing religious freedom in the workplace : legal models -- The effect of the European Convention on Human Rights and its application -- The legislative and policy landscape in England and Wales -- Negative manifestation -- Passive manifestation -- Active manifestation -- Conclusion.
Includes bibliographical references (pages 243-252) and index.
Keywords: Religion in the workplace -- Law and legislation -- United Kingdom; Discrimination in employment -- Law and legislation -- United Kingdom; Freedom of religion -- United Kingdom; Labor laws and legislation -- United Kingdom